Benefits for Women in Nile Economic Development - World Bank Group (World Bank, Entebbe, 2016)
Women and girls often risk being left behind in development, not being fully informed or involved in decision making about issues that can have a real impact on their lives. Sometimes, they are already disadvantaged by cultural and legal norms that affect their rights to resources. Working together to develop the Nile resource, the 10 countries involved in the Nile Basin Initiative (NBI) are making it ‘business as usual’ to ensure gender equality in the economic benefits emerging from their shared efforts.